Pengaruh Harga, Kualitas Pelayanan, dan Costumer Relationship Management Terhadap Keputusan Pembelian Pada Asuransi Astra (Garda OTO) - Dhita Adriani Rangkuti; Mey Monita Lestari Manalu; Sartika Nanda Lestari; Brian Robuli; Irfan Boy Samosir (COSTING : Journal of Economic, Business and Accounting, 2021)
The purpose of this study was to determine and analyze the effect oprice, service quality, and customer relationship management on the purchase decision of Asuransi Astra Garda OtoMedan, JL.ImanBonjol. The data used are primary data obtained from the answer of 85 respondents by accidental sampling method. Data collection techniques used in this study used a questionnaire and interview technique. Data analysis techniquesin the study used linear regression, classic assumption tests, hypothesis testing (t test and f test) and the coefficiecnt of determination. Hypothesis testing results indicate that partially (t) obtained value for t count price of 2,833 > t table 1,658 and sig value obtained 0,005<0,05 which means that price has a positive and significant influence on purchasing decisions in using Astra Insurance services (Garda Oto). Partially obtained value for service quality tcount 5.152 >ttable 1.658 and sig value obtained 0.000 <0.05 which means that service quality has a positive and significant influence on purchasing decisions in using Astra Insurance (Garda Oto) services, partially obtained value for customer relationship management t count 8.878 > 1.658 t table and the sig value obtained is 0.000 <0.05 which means that customer relationship management has a positive and significant influence on purchasing decisions in using Astra Insurance (Garda Oto) services, for the F test results obtained calculated F value = 77.769 > f table (2.69), and a significance probability of 0.000 <0.05, meaning that simultaneously prices, service quality and customer relationship management have a positive and significant effect on purchasing decisions in using Astra Insurance Services (Garda Oto). Keywords: Price, Service Quality, and Customer Relationship Management.